The Effect of Ratio Germinatic Soybean Flour with Tapioca and Ratio of Chicken with Puree of Bambooshoot on the Quality of Bambooshoot Nugget - Maisyarah Parinduri; Herla Rusmarilin; Lasma Nora Limbong (Universitas Sumatera Utara, 2016)
Nugget is a snack served with the rice that made from animal material rich for protein such as chicken. The aim of this research was to find the effect of ratio germinatic soybean flour with tapioca and ratio of chicken with puree of bamboo shoot on the quality of bamboo shoot nugget. This research was conducted using completely randomized design with two factors, i.e ratio of germinatic soybean flour with tapioca (T): (20%:80%, 40%:60%, 60%:40%, 80%:20%) and ratio of chicken with puree of bambooshoot (R): (1:1, 1:0,8, 1:0,6, 1:0,4). Parameters analyzed were moisture content, ash content, fat content, protein content, crude fiber content, organoleptic value of flavor, texture, taste, and color. The results showed that the interaction between ratio of germinatic soybean flour with tapioca and ratio of chicken and puree of bambooshoot had a significant effect (P<0,05) on moisture content, organoleptic value of flavor, and texture. The increasing concentration of germinatic soybean flour increased the ash content (%), fat content (%), protein content (%), and crude fiber content (%) but decreased the moisture content (%) and organoleptic values. The decreasing concentration of puree bambooshoot decreased the moisture content (%), ash content (%), crude fiber content (%), and organoleptic value of texture, but increased the fat content (%) and protein content (%). The ratio of germinatic soybean flour with tapioca of 60%:40% and ratio of chicken with puree of bamboo shoot of 1:0,6 produced the best bamboo shoot nugget. Keywords: Germinatic soybean flour, tapioca, chicken, puree of bamboo shoot, nugget.